Pro-atherogenic role of smooth muscle Nox4-based NADPH oxidase. (March 2016) - Tong, Xiaoyong; Khandelwal, Alok R.; Wu, Xiaojuan; Xu, Zaicheng; Yu, Weimin; Chen, Caiyu; Zhao, Wanzhou; Yang, Jian; Qin, Zhexue; Weisbrod, Robert M.; Seta, Francesca; Ago, Tetsuro; et al.
Abstract: Nox4-based NADPH oxidase is a major reactive oxygen species-generating enzyme in the vasculature, but its role in atherosclerosis remains controversial. Objective: Our goal was to investigate the role of smooth muscle Nox4 in atherosclerosis. Approach and results: Atherosclerosis-prone conditions (disturbed blood flow and Western diet) increased Nox4 mRNA level in smooth muscle of arteries. To address whether upregulated smooth muscle Nox4 under atherosclerosis-prone conditions was directly involved in the development of atherosclerosis, mice carrying a human Nox4 P437H dominant negative mutation (Nox4DN), specifically in smooth muscle, were generated on a FVB/N ApoE deficient genetic background to counter the effect of increased smooth muscle Nox4. Nox4DN significantly decreased aortic stiffness and atherosclerotic lesions, with no effect on blood pressure. Gene analysis indicated that soluble epoxide hydrolase 2 (sEH) was significantly downregulated in Nox4DN smooth muscle cells (SMC), at both mRNA and protein levels. Downregulation of sEH by siRNA decreased SMC proliferation and migration, and suppressed inflammation and macrophage adhesion to SMC. Conclusions: Downregulation of smooth muscle Nox4 inhibits atherosclerosis by suppressing sEH, which, at least in part, accounts for inhibition of SMC proliferation, migration and inflammation. Highlights: Atherosclerosis-prone conditions increase Nox4 in smooth muscle of arteries. Smooth muscle Nox4 plays a detrimental role in the development of atherosclerosis. Downregulation of smooth muscle Nox4 inhibits atherosclerosis by suppressing sEH. Nox4 regulates SMC proliferation, migration and inflammation via sEH.